Natural plants in hospitality servicescapes: the role of perceived aesthetic value. Issue 2 (3rd February 2020) - Apaolaza, Vanessa; Hartmann, Patrick; Fernández-Robin, Cristobal; Yáñez, Diego
Abstract : Purpose: This paper aims to examine the effects of natural plants on satisfaction and loyalty in the hospitality servicescape and provides a theoretical framework explaining the underlying processes. Design/methodology/approach: An experimental study (plants vs no-plants) was conducted in a restaurant with a sample of 119 individuals. Data were analyzed using ANOVA and bootstrapping moderated mediation analysis (Hayes, 2013). Findings: The results of the study confirmed significant effects of indoor natural plants on consumers' satisfaction and loyalty, mediated by the experiential value components of aesthetic value, service excellence and escapism. The absence of an interaction of these influences with consumers' connectedness to nature indicates that the beneficial effects of indoor plants universally affect all individuals, independent of their personal degree of feeling connected with nature. Practical implications: Indoor natural plants as ambient elements in restaurants can improve satisfaction and loyalty by enhancing the dimensions of aesthetics and escapism of the service experience, as well as the perception of service quality. Originality/value: This is the first experimental study analyzing the effects of indoor plants on customer satisfaction and loyalty conducted in a real-life restaurant setting using actual plants. The findings contribute theoretically by providing an integrated conceptual model of the satisfaction and loyalty effects of atmospheric stimuli (i.e. plants) in the hospitality servicescape, which offers a process explanation based on the mediating influence of aesthetic value and the sequential mediations of aesthetic value → service excellence and aesthetic value → escapism.